2007
DOI: 10.1210/jc.2006-1711
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors and Ultrasound Evaluation of Intima-Media Thickness at Common Carotids, Carotid Bulbs, and Femoral and Abdominal Aorta Arteries in Patients with Classic Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency

Abstract: A reduced insulin sensitivity and increased IMT were demonstrated in adults with CAH, who consequently need a follow-up for cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
118
7
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(146 citation statements)
references
References 16 publications
11
118
7
3
Order By: Relevance
“…Single blood pressure measurements in adult CAH, mainly in females, have found values similar to controls (20,21) or elevated (23). No differences from controls were found by us in 24 h ambulatory measurements with the exception of one genotype group (see below).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Single blood pressure measurements in adult CAH, mainly in females, have found values similar to controls (20,21) or elevated (23). No differences from controls were found by us in 24 h ambulatory measurements with the exception of one genotype group (see below).…”
Section: Discussionsupporting
confidence: 55%
“…Our patients had increased insulin release during the OGTT and older patients tended to have higher HbA1c than younger ones, suggesting an increased risk of T2DM in the older CAH males. Insulin resistance has been found in adult CAH by all investigators (6,8,9,12,13,18,(20)(21)(22)(23), but one (18) and has most commonly been expressed as homeostasis model assessment (HOMA) index. We did not calculate this index because fasting glucose was low in our patients, which may lead to a falsely low estimation of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the few studies that have explored insulin sensitivity in CAH, most have concluded that CAH patients are indeed characterized by insulin resistance (5)(6)(7)(8)(9)(10)(11). Many different methods have been used to assess insulin sensitivity, but studies using the euglycemic hyperinsulinemic clamp method, the gold standard to assess insulin sensitivity, are lacking.…”
Section: Introductionmentioning
confidence: 99%